Impact of temporal and rearing environment variations on brood ester pheromone production in the honey bee Apis mellifera - Mondet, Fanny; Beslay, Dominique; Cousin, Marianne; Le Conte, Yves (Comptes Rendus. Chimie)
Chemical communication plays a key role in homeostasis within social insect societies. The development of the superorganism relies on the tightly regulated raising of new individuals, which necessitates an efficient communication system between the brood and adult workers. In the honey bee Apis mellifera, a blend of ten fatty-acid esters found on the cuticle of larvae ensures such successful brood development. This brood ester pheromone (BEP) has both releaser and primer effects on honey bee workers. In this study, we investigated the temporal variations of BEP under natural conditions as well as the developmental variations of the 10 compounds for in-hive versus in vitro reared brood. We identified marked monthly changes in the composition of BEP throughout the season, with an increase in total amounts in the fall characterised by an enrichment in ethyl esters. Drastic changes in the amount of BEP were confirmed during development, with a peak during the last larval stage. Comparison between in-hive and in vitro reared bees showed that individuals harbour very similar BEP profiles during the larval stage, but distinct profiles during the pre- and pupal stages. This study validates the use of in vitro rearing methods for studying the chemical ecology of honey bee larvae and increases our understanding of the ecophysiology of one of the most important pheromones of honey bee colonies.